The Healthy Nasal Cavity—Characteristics of Morphology and Related Airflow Based on a Statistical Shape Model Viewed from a Surgeon's Perspective - Hildebrandt, Thomas; Brüning, Jan Joris; Schmidt, Nora Laura; Lamecker, Hans; Heppt, Werner; Zachow, Stefan; Goubergrits, Leonid (Facial Plastic Surgery, 2019)
Functional surgery on the nasal framework requires referential criteria to objectively assess nasal breathing for indication and follow-up. This motivated us to generate a mean geometry of the nasal cavity based on a statistical shape model. In this study, the authors could demonstrate that the introduced nasal cavity's mean geometry features characteristics of the inner shape and airflow, which are commonly observed in symptom-free subjects. Therefore, the mean geometry might serve as a reference-like model when one considers qualitative aspects. However, to facilitate quantitative considerations and statistical inference, further research is necessary. Additionally, the authors were able to obtain details about the importance of the isthmus nasi and the inferior turbinate for the intranasal airstream.
Keywords: statistical shape model; nasal cavity; nasal breathing; nasal airflow; isthmus nasi; inferior turbinate